Beauty and the Golden Ratio - Copertari, Luis F.; Reyna, Gloria V. (Advances in Social Sciences Research Journal, 2022)
The ideas of beauty and, specifically, female facial beauty, are developed in depth in this paper, in light of the adjustment of facial beauty to the golden ratio according to the parameters defined for such purpose. An experimental design of our own is made, software for carrying out the experiments is developed and the experimental results are analyzed for both male and female population from the Computer Engineering Program of the Autonomous University of Zacatecas (UAZ) and the Psychology Department, also at UAZ. It is concluded that women are more sensitive than men to the aesthetics dictated by the conformance to the golden ratio. Also, we conclude that the golden ratio does play an important role in female facial beauty perception.